2001
DOI: 10.1038/modpathol.3880309
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cysteine Proteinases Cathepsins B and K and of Cysteine Proteinase Inhibitor Cystatin C in Giant Cell Tumor of Tendon Sheath

Abstract: The expression of cysteine proteinases cathepsins B and K and of the endogenous inhibitor of cysteine proteinases, cystatin C, was investigated in tissue specimens of patients with giant cell tumor of tendon sheath (GCTTS). Expression of both enzymes was examined by immunohistochemistry in tissue specimens of 14 patients with GCTTS. Applying double-labeling techniques, the coexpression of cathepsin B and its major endogenous inhibitor cystatin C was additionally studied. Cells expressing the respective protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…However, several studies indicate a predominant expression of cathepsin K in osteoclasts and osteoclast-like giant cells (12,14,15,(31)(32)(33)(34). In the present study, staining of this proteinase was strong in osteoclasts at sites of bone destruction and in multinucleated giant cells of the perimatrix, whereas only few mononuclear cells in this region were detected.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…However, several studies indicate a predominant expression of cathepsin K in osteoclasts and osteoclast-like giant cells (12,14,15,(31)(32)(33)(34). In the present study, staining of this proteinase was strong in osteoclasts at sites of bone destruction and in multinucleated giant cells of the perimatrix, whereas only few mononuclear cells in this region were detected.…”
Section: Discussioncontrasting
confidence: 51%
“…Microscopic evaluation of the slides was performed according to previously described methods (15). Cell types were monitored as nonaffected chondrocytes, surrounding connective tissue, and external ear canal skin (NT); keratinized squamous cholesteatoma epithelium, i.e., matrix ( …”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemically, cystatin C protein was stained intracellularly in the cytoplasmic compartment of tumour cells in a variety of cancer types (Lignelid and Jacobsson, 1992;Lignelid et al, 1997;Yoshimura et al, 2000;Gaumann et al, 2001;Hansen et al, 2001;Yano et al, 2001). The mechanisms controlling the intracellular inhibition of cysteine proteinases in endosomes and lysosomes with cystatin C entering the endosomal -lysosomal pathway by endocytotic uptake may include dimerisation (Ekiel and Abrahamson, 1996;Merz et al, 1997), proteolytic fragmentation by cathepsin D (Lenarčič et al, 1991) or neutrophilic granulocyte elastase (Abrahamson et al, 1991).…”
mentioning
confidence: 99%
“…These are particularly found to destroy the proteins of the cellular matrix, such as collagen and lamina, and are therefore involved in the invasion and metastasis of some malignant tumors (13-16). numerous studies have reported that lysosomal cysteine protease cathepsin is highly expressed in human and murine tumor tissues (10,17,18) and sera (9). in certain studies, lysosomal cysteine protease cathepsin cdna was transferred into tumor cells, increasing tumor cell metastasis, while in other studies, lysosomal cysteine protease cathepsin genes were knocked out or rna interference technology was used for cysteine protease cathepsin genes (19-21), decreasing tumor cell invasion in matrigel in vitro, preventing solid tumor formation and inhibiting angiogenesis in a mouse model or in tumor cells.…”
Section: Discussionmentioning
confidence: 99%